A case of double-outlet left ventricle with atrioventricular discordance - (:unkn) unknown (TURKISH J PEDIATRICS, 2005)
The clinical, echocardiographic and angiographic aspects of a four-month-old boy with double-outlet left ventricle, atrioventricular discordance, L-malposition of the great arteries, ventricular septal defect and pulmonary stenosis are described. Additionally, in this patient, the right arcus aorta and the ligament of ductus arteriosus caused anterior compression of the trachea. The anterior position of the morphological left ventricle is the most interesting feature.
Keywords: double-outlet left ventricle; atrioventricular discordance; vascular ring; MORPHOLOGY; DIAGNOSIS